Optimalisasi Produksi Batubara dengan Meminimalisir Coal Loose pada Area Pit Penambangan di PT. Artamulia Tatapratama - Cici Wulandari; Adree Octova (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. Coal Mining Activities at PT. Arta Mulia Tata Pratama is implementing an open pit system. Coal getting activity is one of the mining activities at PT. ATP. Before doing the activities, coal getting coal volume must be known first. It is for knowing how much the actual volume of coal is measured on the floor and roof on material that will be mined. The actual volume is 186.528.0 tons. while the planned plant of the company is 189.525.0 tons. This indicates that no fulfillment  2,997 tons of coal production targets in the month of January 2018.In coal extraction activities can be happend loose (lost / wasted) of coal material. cleaning on the coal floor, coal damage, and slope mismatch. These factors must be assessed to see the contributions of the waste of coal material and analyzed problems. It is aimed to get accurate data and increase the recovery. This method uses the fishbone method that aims to analyze the problems in the causal factors of coal loose. it is found that the loose contribution of coal loose on the clean floor coal is 890,786tons, loose contribution to coal damage is 89.86 tons, and coal loose contribution to slope is 1.824,615tons.Keywords: coal loose, cleaning floor, coal damage , slopes, fishbone